Etnografi Virtual Budaya Belajar Melalui Media Online - Kulzum, Putri Maja Mulia; Asmuni , Hadiqoh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2024)
Abstract: Times are increasingly developing, as is technology which is developing rapidly with various kinds of sophistication that many people can use to help us in our daily activities. With the help of technology, everything that was initially impossible starts to become easy. Additionally, technological advances have made it easier for humans to carry out their daily tasks, such as shopping and traveling. Like online media or cyber media in general, it is a type of communication that occurs on the internet which is carried out through websites; this can include text, photos, video, and audio. In other words, all types of communication that occur on the internet are called online media. Likewise, with learning activities both in schools and universities, educators are greatly helped by the existence of advanced technology such as online media which is widely available as a medium and learning resource for students. This research uses an ethnographic method known as virtual ethnography to investigate the social and cultural phenomena of users in cyberspace. Virtual ethnography is a type of qualitative research that uses multiple systems of inquiry rather than logical and statistical procedures. Qualitative research attempts to carry out a naturalistic inquiry process to seek an in-depth understanding of social phenomena in their natural environment. It centers on the “why” rather than the “what” of social phenomena and relies on the direct experience of humans as meaning-making agents in their everyday lives. The author made observations for one year and conducted interviews with several lecturers and students regarding current learning using online media. From the research results, the many advantages that online media currently have are indeed helpful for lecturers and students, but behind this there are also weaknesses.